Lipid Quantity, Composition and Provisioning in the New Zealand Snapper/Tamure Chrysophrys Auratus - Allen, Hamish (Auckland University of Technology, 2017)
Snapper (Sparidae: Chrysophrys auratus) are a demersal teleost, and are one of the most abundant and ecologically important species inhabiting coastal New Zealand waters. They are highly valued both commercially and recreationally, and are under continuing pressure from intensive fishing efforts. This has led to declines in genetic diversity amongst populations, changes in the ecosystem structure of reef communities, and a significant reduction in stock biomass. Lipids and fatty acids are fundamentally important for growth, as sources of metabolic energy, in the structure and integrity of cell membranes and as endogenous energy reserves for the purpose of reproduction. Within a population, the quantity and concentration of an individual’s lipids and fatty acids can vary significantly. During reproduction, older and larger individuals can produce larvae that are larger, grow faster and survive periods of starvation for longer, compared to larvae of smaller, younger individuals, due in part to a greater provisioning of energy rich and biologically important lipids. The composition of lipids may also vary; an important aspect as lipids such as triglycerides and certain fatty acids, play more integral roles than others in developmental processes. It has been alleged that maternal age can have profound impacts on embryonic, larval and juvenile survival, growth rates, and functionality. We investigated triglyceride and fatty acid profiles of female New Zealand snapper/tamure (Chrysophrys auratus) across age, size, and condition, throughout its spawning season between November 2015 and February 2016. A total of 113 Chrysophrys auratus were sourced from the Hauraki Gulf Marine Park, North Island east coast, New Zealand. Individuals were measured, aged and histologically staged, before High Pressure Liquid Chromatography was used to determine triglyceride concentrations in female liver and gonad tissue, and Gas Chromatography to determine fatty acid concentrations in female gonad tissue. Results determined that maternal influences such as size, age, and condition, are not influencing lipid composition or concentrations. Therefore, the quality of oocytes is likely to be comparable across the population, placing importance on larger individuals whose fecundity is exponentially greater than that of their smaller counterparts. In addition to this, snapper appear to demonstrate a tendency towards a capital breeding strategy, using (to some degree) stored lipid reserves to fund reproductive needs across multiple spawning events. This removes any reliance on specific food sources being available at specific times, and affords adaptability in the timing of spawning, enabling reproduction to take place when it is environmentally optimum, and has likely been a contributing factor in the success and abundance of this species.
Keywords: Chrysophrys auratus; Fatty acids; Lipids; Snapper; Spawning; Triglycerides